Design and development of automated guided vehicle at the manufacturing and assembly floor - Mohamad Nasreeq Ahmad, 1994-, author 610437; Nur Safwati Mohd. Nor, supervisor 502929; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017